2021
DOI: 10.5603/fm.a2020.0027
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the innervation of the dorsal wrist capsule using modified Sihler’s staining

Abstract: Background: The aim of this study was to assess the innervation of the dorsal articular capsule of the wrist using modified Sihler's staining. Materials and methods: Thirty dorsal wrist capsules were collected from 15 donors (both sides) within 12 hours of death. All the capsules were collected in the same mannerusing the dorsal incision. The specimens were stained according to the protocol of the modified Sihler's staining technique. The preserved capsules were analyzed under 8-16× magnification of an optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Terng et al 51 reported that wrist hyperextension results in entrapment of excess subcapsular soft tissue in the midcarpal joint, resulting in dorsal wrist pain. Sgromolo et al 48 reported that excision of the posterior interosseous nerve, innervating the midcarpal joint and within the wrist capsule, 7 improves dorsal wrist pain. Furthermore, there is a case report in which wrist pain was intensified by wrist hyperextension, and dorsal lunocapitate impingement was found on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Terng et al 51 reported that wrist hyperextension results in entrapment of excess subcapsular soft tissue in the midcarpal joint, resulting in dorsal wrist pain. Sgromolo et al 48 reported that excision of the posterior interosseous nerve, innervating the midcarpal joint and within the wrist capsule, 7 improves dorsal wrist pain. Furthermore, there is a case report in which wrist pain was intensified by wrist hyperextension, and dorsal lunocapitate impingement was found on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This nerve innervates the dorsal joint capsule [12]. Recently, in their histological study of the dorsal wrist capsule, Bonczar et al showed the PION innervated 60% of the central portion; the remaining area was innervated by the superficial branch of the radial nerve and the medial antebrachial cutaneous nerve [13].…”
Section: Discussionmentioning
confidence: 99%
“…More distally, it has a nervous connection with a branch of the PIN and innervates the dorsa of the CM joints of the fourth and fifth fingers. The MACN also innervates ~25% of the wrist capsule from the ulnar side (Bonczar et al, 2020).…”
Section: Methodsmentioning
confidence: 99%